"Equal rites before the law": religious celebrations of same-sex relationships in the Netherlands, 1960s–1990s. Issue 3 (2nd September 2017) - Bos, David J.
ABSTRACT: The opening-up of marriage to same-sex couples, which became Dutch law in 2000–2001, is often presented as a triumph of emancipation and secularization. Well into the 1990s, however, the majority of Dutch LGB organizations would have none of it – whereas Catholic and mainline Protestant initiatives at solemnizing homosexual relationships had been taken already since the 1960s. After explaining progressive, secular objections to marriage, this article discusses a number of more or less official, clerical initiatives at public, ritual recognition of same-sex relationships from the 1970s and 1980s. Next, as a historical backdrop, it sketches the emergence of a pastoral discourse on "the homophile neighbor" since the late 1950s. Lastly, it discusses three highly publicized "stunts" from 1967 to 1970. It is argued that religious institutions and traditions have not only posed an obstacle to non-heterosexuals, but offered them a repertoire of symbolic expression and contestation.